Twenty-Five Years of the International Review of Research in Open and Distributed Learning: A Bibliometric Analysis - Torres-Vergara, Carlos J.; Alfaro-García, Victor G.; Merigó, José M.; Atif, Amara; McGreal, Rory (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
The International Review of Research in Open and Distributed Learning (IRRODL) published its first issue in 2000. This paper provides an overview of the journal’s development over its 25-year history using bibliometric indicators. We analyzed IRRODL’s performance relative to other journals in the field and have highlighted key contributing countries, institutions, and authors based on the Scopus database. Our approach used various bibliometric techniques, including the number of articles and citations, cites per paper, and the h-index. The findings reveal that IRRODL is a leading journal in open and distributed learning, attracting a diverse group of authors from institutions and countries worldwide. Currently, Athabasca University is by far the most productive university, and the United States and Canada are the most productive countries appearing in the journal. However, the journal is very diverse with publications from all over the world.